Current methods and new approaches to assess aqueous humor dynamics. (4th May 2021) - Toris, Carol B.; Gagrani, Meghal; Ghate, Deepta
ABSTRACT: Introduction: Aqueous humor and its dynamics (AHD) serve numerous functions to sustain ocular health and clear vision. Current methods to assess AHD have led to improved understanding of ocular physiology, pathologies caused by abnormal intraocular pressures (IOP), and treatments to return IOP to healthy levels. However, the assumptions and limitations inherent in these methods have been problematic. New methods on the horizon are showing promise to greatly advance the field. Areas covered: This review summarizes AHD assessment techniques in use today including the noninvasive methods of fluorophotometry, tonometry, tonography, venomanometry, and invasive methods of cannulation, infusion, dissection. It also mentions emerging methods utilizing advanced imaging methods, smart phones, cameras, and software. Expert opinion: Soon new techniques will become available to measure each parameter and even subparts of each parameter of AHD with increased speed, accuracy, and safety. Along with these new methods and the data they generate could emerge the next version of the Goldmann Equation. These new methods would make AHD an important tool in the clinic for precision medicine and in the lab for exploring AHD on a new level.